Integrating Food Processing Technology in Chemical Engineering Undergraduate Teaching - Ching Lik Hii (Dept. Food Technology, Faculty of Animal and Agricultural Sciences, Diponegoro University, 2021)
Chemical engineering and food processing are two individual disciplines that are related to each other in many scientific and engineering principles. However, food processing is not widely taught in a typical chemical engineering curriculum. In this paper, an overview of the Food Processing Technology subject taught in the Department of Chemical and Environmental Engineering, University of Nottingham Malaysia is presented and discussed with lecture application examples and outcome of assessments based on the Engineering Accreditation Council guideline (Malaysia). The outcome of the assessment will be based on the recent academic session for the year 2019-2020. Attainment of students is also evaluated based on learning outcomes (LO) and program outcome (PO) analyses. The purpose of this evaluation is to reflect and improve the curriculum and for continuous quality improvement purposes which is the key process in accreditation and also to enhance student’s learning experience.